Blast off for leo - Liddell, Eric; Creative department (Cairo educational services company, 2023)
Leo and his robort, travel through space to search for numbers. from the window of their rocket, they have a great view. find out what things they see. how many numbers do they discover?
Arithmetic notions
Keywords: Mathematics